PJMHS 2021
DOI: 10.53350/pjmhs2115103397
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Maternal and Fetal Outcome in Obese Non- Obese Pregnant Women

Abstract: Objective: The aim of this study is to determine the adverse pregnancy outcomes in obese and non- obese women. Study Design: Randomized controlled trial Place and Duration: Department of Gyne & Obs, Shahida Islam Teaching Hospital Lodhran, during from 01-07-2020 to 31-07-2021. Methods: Total one hundred and eighty patients were enrolled in this study. Patients were aged between 18- 50 years. Patients detailed demographics were recorded after taking written consent. Patients were equally divided into two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…Similarly, preeclampsia hypertension, preeclamptic toxemia (PET), and eclampsia were 3.5 times, 2.8 times, and 4.5 times higher for overweight pregnant women than non-overweight pregnant women in India [14,25]. In Pakistan, PET, in obese pregnant women was more than 15% higher compared to normal-weight pregnant women, eclampsia was three-fold greater in obese women, and gestational diabetes mellitus was higher at 23.3% as compared to 6.7% in non-obese [26].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Similarly, preeclampsia hypertension, preeclamptic toxemia (PET), and eclampsia were 3.5 times, 2.8 times, and 4.5 times higher for overweight pregnant women than non-overweight pregnant women in India [14,25]. In Pakistan, PET, in obese pregnant women was more than 15% higher compared to normal-weight pregnant women, eclampsia was three-fold greater in obese women, and gestational diabetes mellitus was higher at 23.3% as compared to 6.7% in non-obese [26].…”
Section: Discussionmentioning
confidence: 84%
“…Older age pregnant women are more likely to develop thyroid dysfunction, pregnancy complications, and congenital or neurocognitive fetal complications [15,26,27]. However, other studies have suggested that obesity, primiparity, and younger age had abnormal levels of FT4 at all trimesters, higher TSH, pregnancy complications, and offspring problems [27,28].…”
Section: Discussionmentioning
confidence: 99%